DEVELOPMENT OF GOOGLE SITES WEB-BASED IPAS LEARNING MEDIA TO IMPROVE TEACHER PEDAGOGICAL COMPETENCE - Iis Narahmalia; Andrian Gandi Wijanarko; Farinka Nurrahmah Azizah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper demonstrates the product in the form of Google Site web-based Natural Science learning media to improve teachers' digital pedagogical skills. The research type is research and development (R&D) with the ADDIE model, which consists of five steps or stages, namely analysis, design, development, implementation, and evaluation. The participants consisted of 21 students and 17 teachers in grade IV SD Universal Temanggung. Data collection techniques were interviews, observations, and questionnaires. The validation test results from two validators, namely media expert and material expert validators. Based on the media expert validators, an average percentage was 81% interpreted into the very feasible category. Of the material expert validator, the average percentage value was 79% in the feasible category. The increase in digital pedagogical competence was 88.5% with a very feasible category in making educational content creation that increased 15%. Based on the data, it can be concluded that the development of Google Site web-based Natural Science learning media can improve teacher's digital pedagogical competence.Â Â